How do stakeholders evaluate smart specialization policies defined for their regions?. Issue 3 (23rd November 2020) - Farinha, Luís; Lopes, João; Sebastião, João Renato; Ferreira, João José; Oliveira, José; Silveira, Paulo
Abstract : Purpose: This paper aims to understand how the different stakeholders assess the adequacy of smart specialization policies defined for their regions. Design/methodology/approach: This paper has followed a quantitative methodology through the application of questionnaire surveys to stakeholders of the various territorial regions in Portugal. Findings: As a result, from the "resource-based view" approach applied to the various regions, the attained results highlight that the suitability of smart specialization policies defined for the Portuguese regions is not unanimous among its stakeholders. Originality/value: The research can be used as a tool to assist regional policymakers in strategic reflection when defining and adjusting smart specialization strategies in their territories.